Komunikasi Pembangunan Masyarakat: Sebuah Model Audit Sosial Multistakeholder - Teuku Zulyadi (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2018)
National programs involving central and local government are complex issues. The length of bureaucracy and the involvement of many parties have its own independence, such as overlapping central and regional rules. Another problem will arise that is loosening the hands of the parties, so the public does not know for sure the base of the problem. This study aims to examine the concept of social audit involving the parties in the development process. Social audit is a form of broad community participation to measure the accountability and integrity of government programs. This study focuses on the program flow that includes budget transfers, distribution, reporting and complaint mechanisms. More details, reviewing the availability of rules, program implementation and community access. This concept is appropriate to test government policy on social assistance programs for all levels of community groups. Problem mapping and dialogue to find common solutions are the advantages of this social audit concept. The study was conducted by literature study approach on social audit tools of integrity system development program and accountability process from government budget on education sector, agriculture and social welfare of Pattiro NGO.